Magnetic properties of Cu1+xMn2-xO4 and Ni1+xMn2-xO4 solid solutions - Pena, O.; Cailleaux, X.; Piriou, B.; del Canto, M.; Abarca, S.; Rios, E.; Ortiz, J.; Gautier, J. L.; Lisboa Filho, Paulo Noronha [UNESP]; Moure, C. (Elsevier B.V., 2007)
Magnetic properties of two spinel oxides solid solutions, Cul+xMn2-xO4 and Ni1+xMn2-xO4 are reported. These series are characterized by two magnetic transitions: the upper one, of ferrimagnetic type, occurs at about 85 K (for copper-based) and at 105-110 K (for nickel-based spinels), independently of the x-content: the lower transition may be related to a Neel-type collinear ordering and takes place at 30 and 45 K, respectively. Application of moderate fields (H > 250 Oe) make both transitions to merge into one broad maximum in the magnetization, which takes place at lower temperature when applying larger fields. Magnetization cycles with temperature (ZFC/FC) or field (loops) allowed us to well characterize the ordered state. The effective moment follows the expected behavior when manganese ions are being substituted by ions of lower magnetic moment (Ni(2+)andCU(2+)). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: spinels; magnetic properties; soft magnets; ferrimagnetism